HUBUNGAN SIKAP PNS PEMERINTAH KOTA BANDUNG TERHADAP REWARD DAN PUNISHMENT DENGAN KOMITMEN ORGANISASI - Capriaty Ciciliany Andre; M. Banowati Talim (Universitas Kristen Maranatha, 2018)
Reinventing government is the first step in transforming public organization to be more professional and efficient by creating and improving the workers’ quality (Osborne & Gaebler, 2014). Therefore, this study was conducted to determine the correlation of workers’ attitudes towards reward and punishment linked to organizational commitment. The 276 samples were obtained using cluster sampling. Data were collected through questionnaires and in-depth interviews. The results showed that the variables are inversely correlated. The workers are unsatisfied with the current rewards and punishment system. The implementation of reward and punishment’s regulations are only as formality, subjective, and it does not meet the aspect of fairness. Researcher suggests to conduct a more objective assessment of the workers’ performance. Keywords: Attitude, Reward, Punishment, Organizational Commitment, Organization Behavior, Government Workers.